China’s Elite Tertiary Education - Guo, Congbin (International Higher Education, 2020)
During the past 25 years, China's elite higher education system has been systematically developed and supported by constructive projects, such as Project 211 & 985, C9 League, and the Double First-Class Plan. China's elite universities have also proliferated during this process, and some of them are already rated among the world's top universities. This article gives a general introduction to China's elite higher education projects.